Swimming as Treatment of Scapular Dyskinesis - Max Rogerio Freitas Ramos; Yonder Archanjo Ching San Junior; Leonardo Antunes Bellot de Souza (Case Reports in Orthopedics)
Scapular dyskinesis is quite frequent and can lead to shoulder pain. The diagnosis is essentially clinical. The main cause is muscle imbalance, between the trapezius, rhomboids, and pectoralis minor. In these cases, rehabilitation is the best treatment. We present a case of a young male patient with dyskinesis due to axonal involvement of the long thoracic nerve and paresis of the anterior serratus muscle. After a swimming program to increase muscular strength and imbalance, he experienced pain reduction and functional recovery of the upper limb, with reduction of the winged scapula.